SUPERVISED CURRICULAR INTERNSHIP: A CASE STUDY ON THE WELCOMING INDICATORS - Lima, Diane Mota [UNESP]; Pinto da Costa, Miguel Ataide; Santos, Jose Henrique dos (Unesp-faculdade Ciencias & Letras, 2021)
This study aimed to identify the indicators of welcome (receptivity model) to the Physical Education intern by his/her Supervising Teacher (ST) during the supervised internship period. The method used was qualitative, case study type, from the perspective of the Descriptive Analytical Model. The participants were a supervising physical education teacher and her intern. The instruments used were semi-structured interviews, on-site observations, and final internship report, all analyzed through the Content Analysis Technique. The results indicated that the Supervising Teacher provided an internship with predominant elements of the Formative Welcoming, prioritizing the partnership and the integration of the intern to the school environment.
Keywords: Internship welcome; Teacher education; Supervised curricular internship; Physical education